PEMBERDAYAAN KELUARGA DALAM MENCEGAH KEGAWAT DARURATAN STROKE DENGAN DETEKSI METODE FACE, ARMS, SPEECH, TIME (FAST) TERHADAP PENGETAHUAN DAN SIKAP - Frana Andrianur; Ismansyah Ismansyah (Poltekkes Kemenkes Kalimantan Timur, 2021)
ABSTRACT Stroke emergencies need to be detected by families to reduce disability and death, so families need to be empowered in caring for stroke patients. Efforts are made to meet the knowledge, attitudes. This study aims to determine the effect of family empowerment as a caregiver in detecting stroke emergencies using the face, arms, speech, time (FAST) method. The design of this study used a quasi-experimental design with one group pretest-posttest. Respondents were taken by consecutive sampling as many as 30 families as caregivers in the Bengkuring Health Center area, Samarinda City. Data were collected using the instrument sheet and knowledge questionnaire, attitude. Data analysis used the Wilcoxon test and the dependent t-test. The results showed that there was a difference before and after the knowledge score (p = 0.000), attitude score (p = 0.000). The instruments used to measure differences in this study are standard, valid and reliable. Empowerment of families as caregivers in the detection of stroke emergencies with the detection of the face, arms, speech, time (FAST) method has been shown to affect increasing knowledge and positive attitudes towards families as caregivers for stroke patients. Family understanding in detecting stroke emergencies is a nursing intervention to increase knowledge, positive attitudes in families who care for stroke patients. ABSTRAK Kegawat daruratan stroke perlu dideteksi oleh keluarga untuk mengurangi kecacatan dan kematian, sehingga kelurga perlu diberdayakan dalam merawat pasien stroke. Upaya yang dilakukan untuk memenuhi pengetahuan, sikap. Penelitian bertujuan untuk mengetahui pengaruh pemberdayaan keluarga sebagai caregiver dalam deteksi kegawat daruratan stroke dengan metode face, arms, speech, time (FAST). Desain penelitian ini menggunakan quasi ekspriment dengan rancangan one group pretest postest. Responden diambil secara consecutive sampling sebanyak 30 keluarga sebagai caregiver di di Wilayah Puskesmas Bengkuring Kota Samarinda. Data dikumpulkan dengan lembar instrumen dan kuesioner pengetahuan, sikap Analisis data menggunakan uji wilcoxcon test dan dependent t-test. Hasil penelitian menunjukkan bahwa ada perbedaan sebelum dan sesudah pada skor pengetahuan (p = 0,000), skor sikap (p = 0,000). Instrumen yang digunakan untuk mengukur perbedaan pada penelitian ini baku, valid dan realible. Pemberdayaan keluarga sebagai caregiver dalam deteksi kegawat daruratan stroke dengan deteksi metode face, arms, speech, time (FAST) terbukti memiliki efek pada peningkatan pengetahuan, sikap postif pada keluarga sebagai caregiver pada pasien stroke. Pemahaman keluarga dalam mendeteksi kegawat daruratan stroke ini merupakan intervensi keperawatan untuk meningkatkan pengetahuan, sikap positif pada keluarga yang merawat pasien stroke.